Distribuição de Mercurio (Hg) em Sedimento, Água e Biota na Região de Influencia dos Efluentes da Carcinicultura na Gamboa do Cumbe - Rio Jaguaribe - Ceará - Brasil - Costa, Breno Gustavo Bezerra (2009)
The Jaguaribe River basin, located in State Ceará, occupies an area of about 80,000 km2, wher as the sub-basin of the Lower Jaguaribe River has a drainage area of 6,875 km2, equivalent to 4.64% of the state’s area. The estuarine region of the Jaguaribe River is dominated by mangrove forests that occupy 215.5 ha, particularly in the tidal channel of the Gamboa do Cumbe. In this area it is located the largest area of shrimp production in captivity in the state, with 1,316 ha of pond area around 50% of the entire aquaculture area of the state of Ceará. The quantification of mercury (Hg) in water and sediments (surface and sedimentary profile) along the Gamboa do Cumbe showed values ranging from 6.3 to 32.1 ng / l (14.4 ± 8.4) , 1.1 to 23.5 ng / l (7.0 ± 7.8), 3.2 to 15.0 ng / l (7.4 ± 3.9), or total Hg, dissolved and particulate Hg respectively. In sediments concentrations ranged from 1.6 to 10.3 ng / g (4.7 ± 2.9) and 1.9 to 16.2% (6.7 ± 4.9) for Hg and organic matter respectively. The concentration of Hg in fish collected in the region ranged from 4.3 to 37.0 ng / g (9.9 ± 9.0) in Testudines sphoeroides and from 9.7 to 66.1 ng / g (31.8 ± 14 , 4) in Cathorops spixii. These data made possible to define the area of preferential deposition and accumulation of Hg and that the predominant form of Hg export is dissolved Hg. Aquaculture, seems to have promoted significant changes in Hg loads in recent years based on records of Hg concentration in sedimentary profiles. Hg of burden from aquaculture to the region is about 156.4 kg.ano-1, mostly associated with TSS transported of the adjacent estuarine region and is stored in the sediment of the deposition area of Gamboa do Cumbe.